Effects of different rootstocks on cadmium accumulation of grafted Cyphomandra betacea seedlings. Issue 12 (26th September 2019) - Liu, Qin; Huo, Rui; Lin, Lijin; Liao, Ming'An; Wang, Jin; Tang, Yi; Liang, Dong; Xia, Hui; Wang, Xun; Lv, Xiulan; Jiang, Wei; Ren, Wei
ABSTRACT: To study whether grafting can reduce the heavy metal uptake of Cyphomandra betacea, C. betacea seedlings were grafted onto three different rootstocks (eggplant, Solanum nigrum, and tomato) and planted in cadmium (Cd)contaminated soil. Compared with ungrafted seedlings, S. nigrum rootstock increased the biomass of different organs of C. betacea seedlings, while eggplant and tomato rootstocks decreased it or had no significant effect. Chlorophyll a, chlorophyll b, and total chlorophyll contents of C. betacea seedlings were ranked as follows: S. nigrum rootstock > ungrafted > eggplant rootstock > tomato rootstock. The three rootstocks had no significant effects on the superoxide dismutase activity of C. betacea seedlings. Solanum nigrum rootstock enhanced the peroxidase and catalase activities and soluble protein content of C. betacea seedlings, while the other rootstocks reduced or had no significant influence on these parameters. The three rootstocks increased the Cd content of aboveground organs of C. betacea seedlings as follows: S. nigrum rootstock > eggplant rootstock > tomato rootstock > ungrafted. Grafting onto S. nigrum rootstock can therefore promote the growth of C. betacea ; however, all rootstocks investigated in this study promote Cd uptake in C. betacea and thus cannot be used in Cd-contaminated areas.